(untitled) (Research, Society and Development, 2020)
Given that violence in Brazil is on the rise, the importance of the odontologist in the Forensic Medical Institutes (IML’s) can be observed, since many injuries occur in the orofacial region and not all IML has a specialist in the area, since there is no requirement for this professional by law. The objective was to establish the importance of the dentist, as an odontolegists, in the diagnosis and elaboration of reports to indicate the type of lesion caused and the anatomical area affected. Epidemiological study of the descriptive type using secondary data collected in the Legal Medical Institute of Cascavel-PR, between the years 2008 to 2017. We collected socio-demographic data of victims; description of oral and maxillofacial lesions regarding type, location and time of occurrence. The data were submitted to descriptive analysis using the Microsoft Excel Program. The results show that men were more affected (51.2%), most of the lesions in adults (28.9%), as to etiology, were mostly caused by physical violence (62.5%). The most common lesions were: Escoriação (28.12%), followed by Equimose (21.21%). There were some inconsistencies regarding the description of lesions in many cases, due to the technical difficulty that a professional, who is not from the dental area, describe the lesions. Bearing in mind that at IML Cascavel there is no dentist, we know the importance of this professional’s participation in the elaboration of reports that can be used judicially for the victim’s benefit, in case he/she needs them. Thus, we conclude the importance of the dentist in the diagnosis and elaboration of reports, in lesions referring to the anatomical region of head and neck.